Black carbon and its impact on air quality in two semi-rural sites in Southern Italy near an oil pre-treatment plant. (15th July 2020) - Pavese, Giulia; Calvello, Mariarosaria; Castagna, Jessica; Esposito, Francesco
Abstract: One-year-long data (October 2017–October 2018) of the equivalent black barbon (EBC), absorption Ångström exponent (AAE), and gaseous compound concentrations in two semi-rural sites in the Agri Valley, Southern Italy, were analyzed. This study aimed to assess the effects of combustion emissions on the air quality and people's health in these sites. The first measurement site, VZI, is located close to the plant, whereas the second is in Grumento, one of the towns at the edge of the valley, approximately 3 km away from the COVA. The emissions mainly originate from the biggest European on-shore pre-treatment plant of crude oil, the Centro Olio Val d'Agri (COVA), which hosts three incinerators and three torches continuously burning. EBC and gaseous pollutants from the COVA mainly affect the area close to the plant. A reduced effect is observed in Grumento where the AAE analysis highlighted the contribution of local domestic heating as an additional source during the cold season. A procedure combining EBC measurements, high-resolution fire satellite visible/infrared imaging radiometer (VIIRS) data, and hybrid single-particle Lagrangian integrated trajectory (HYSPLIT) back-trajectories allowed the identification of the measurement days influenced by both regional and transboundary transport of biomass burning emissions. The identified days were mostly in July, August, and October 2018. The comparison between EBC and PM2.5 data, only available for the Grumento site, showed a good correlation (R 2  = 0.6 on a yearly basis), revealing the relevant contribution of the EBC to the fine particulate matter at the site. Finally, a risk communication methodology was applied to associate the number of daily passively smoked cigarettes (PSC) to the measured EBC concentrations. The daily PSC were 2.8 for VZI, and 1.4 for Grumento, which are closer to the results at the remote sites (0.7) than those at the urban sites (10.1≤ PSC≤ 159.0). Highlights: Comparison of one-year EBC data from two semi-rural sites close to an oil pre-treatment plant (COVA) . Higher concentrations of pollutants from COVA emissions at the site closer to the plant. Additional domestic heating source at Grumento identified via AAE analysis. A procedure to identify the contribution of transboundary biomass burning. Double value of Passively liSmoked Cigarettes (2.8) obtained at COVA plant compared to Grumento (1.4) .